Motivations of Generation Y Administrative Officers: A Case Study of Mahasarakham University - เข็มเพชร, นันทนพ; ช่ำชอง, พบสุข (Journal of Politics and Governance, 2018)
This study aims to investigate motivating factors, including exogenous and endogenous factors, which have an influence on “Generation Y” administrative officers’ engagement in Mahasarakham University. It also aims to explore the way in which administrative officers’ engagement can be sustained and increased. Mahasarakham University is selected as a case study due to its having a large number of “Generation Y” administrative officers. To achieve the objectives, a qualitative study is employed. Regarding data collection, 20 key informants have been selected using a purposive sampling design. In-depth, semi-structured interviews have been conducted to gather data from the key informants. To analyze qualitative data, the analytical framework of the study has been developed from Herzberg’s two-factor motivation theory. A thematic analysis has been conducted. Also, NVivo has been employed to help arrange and analyze the qualitative data. The results show that exogenous factors, namely administrative policy, incentives, and command and control play a vital role in “Generation Y” administrative officers’ engagement in Mahasarakham University. Endogenous factors, namely satisfaction with the working process, performance, and promotion have a partial impact on employees’ engagement. To sustain and improve “Generation Y” administrative officers’ engagement, issues including moral support and incentives at work, a human resource development program, and staff relations should be given high consideration.